Hadith #4479 - Sunan Abi Dawud - Abdullah bin Fyrwz عبد الله بن فيروز الداناج; Ali ibn Abi Talib; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
The Prophet (ﷺ) gave a beating with palm-branches and sandals for drinking wine and Abu Bakr gave lashes. When ‘Umar came to power, he called upon people and said to them: The people are living now near watering placing, and, according to Musaddad’s version, “near villages and watering places, so what do you say about the punishment for (drinking) wine? ‘Abd al-Rahman b. ‘Awf said: We think that you should prescribe the lightest punishment. So he fixed eight lashes for it. Abu Dawud
Grade: Sahih